IMPACT OF TOBACCO EXCISE ON SECTORAL OUTPUT AND GROSS INCOME OF INDONESIA : AN APPLICATION OF INPUT OUTPUT ANALYSIS - Riza Indah Pramesti; Evi Gravitiani (Laboratorium Riset Ekonomi, 2023)
(Excise on Tobacco Products (CHT) as the largest contributor to the Indonesian economy when compared to other excisable goods reaches 96% so it is considered quite effective to improve the country's economy. CHT has increased every year with the aim of controlling the negative impact of cigarette consumption and relaxing the success of the High Risk Excise Control (PBHT) in eradicating illegal cigarettes. This study aims to analyze the impact of the CHT increase on sectoral output and Gross Domestic Product. The method of analysis in this study is Input-Output using the 2010 IO table (updated in 2019). The classification of the Input Output table is 185 sectors and aggregated into 21 sectors. The analysis in this study is multiplier analysis, distribution and linkage. The result is that the increase in CHT on the tobacco product processing industry has no impact on the national economy as a whole, so it is better for the CHT increase regulation to remain in effect. The government must supervise related parties in the production of the cigarette industry so that fraud does not occur if the CHT increase is still in effect.